Analisis perbandingan penerjemahan antara aplikasi legal (Viu) dan Ilegal ( Channel Telegram) pada drama korea "The Penthouse" - dewi, devira kumala (Maliki Interdisciplinary Journal, 2024)
This research compares the translation quality of the Korean drama "The Penthouse" from the Legal (VIU) and Illegal (Telegram Channel) applications. Using 5 samples from each platform, this research aims to find out whether there is a translation comparison between the two types of applications and which of the two is more accurate. The focus of the research is analysis of data sourced from translations of legal and illegal applications, using translation quality theory which includes Accuracy, Acceptability and Readability. As well as comparative analysis. This research includes descriptive qualitative to increase data validation, validation techniques are carried out by increasing the researcher's diligence in observing and analyzing data, including re-reading and in-depth examination of translated texts to ensure consistency and accuracy in evaluation. The results of the research show that there are significant differences In terms of translation quality, the legal application (VIU) provides better translation results compared to the illegal application (Telegram channel).